Pembudayaan Karakter Peduli Lingkungan Melalui Kader Adiwiyata Bagi Siswa SMP Negeri 6 Madiun - Purnamasari, Ika Duwi; Hanif, Muhammad; Pribadi, Dwi Bambang Tulus (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2024)
The Climate Crisis is one of the issues that need attention in the world of education, one of the efforts made is through the adiwiyata program which is followed by schools with certain criteria. The adiwiyata school program is often seen as only being able to be realized by schools that have large land. This study discusses SMP Negeri 6 Madiun with school land in the middle of the city and not widely trying to be able to cultivate the character of caring for the environment through adiwiyata cadres. This study approach uses a qualitative approach with a process of collecting data from observation, interviews, and documentation. The results of the study obtained show that adiwiyata cadres cultivate environmentally caring character for students through (1) the formation of adiwiyata cadres who will be included in working groups with each appropriate criteria, (2) Empowerment of adiwiyata cadres, in the form of motivation, invitation, and example. (3) monitoring and evaluating the activities of adiwiyata cadres through each working group. The study is expected to inspire good practices in cultivating environmental care characters through Adiwiyata School as a form of concern for the climate crisis